CONSTRUCTION OF GROUNDS AND FOUNDATIONS ON BULK SOIL - Bakhromov Mahmud Mamatkhanovich (Journals Park Publishing, 2022)
This article describes the characteristics of cast-in-place soils, their storage time and variation depending on the conditions of origin, the organization of ground and foundation construction, the work done to strengthen the foundation soil or build pile foundations.
Keywords: Bulk soil, types, properties, physical, chemical and biological processes, foundation, soil